2019
DOI: 10.1007/s00125-019-4844-y
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage alterations in islets of obese mice linked to beta cell disruption in diabetes

Abstract: Aims/hypothesis Mild islet inflammation has been suggested as a contributing factor to beta cell failure in type 2 diabetes. Macrophage levels are elevated in the islets of humans and mice with type 2 diabetes, but their effects on beta cells are not understood. Our goal was to examine the gene expression changes in islet-associated macrophages in obesity models with opposing disposition to diabetes development and to assess their potential contribution to beta cell (mal)adaptation. Methods Islets were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Besides the histological staining for the macrophage marker F4/80, the mRNA expression levels of F4/80 ( Adgre1 ) and the other macrophage markers, CD68 and Itgax, are higher in the isolated islets from Glo1 KD mice compared with WT mice. Although these are extensively used as macrophage markers (Marchetti, 2016; Chan et al , 2019; He et al , 2019; Mukhuty et al , 2021), CD68 has been found to be increased in aged and β‐Gal + β‐cells (Aguayo‐Mazzucato et al , 2017, 2019; Ebrahimi et al , 2020). In line with this, CD68 gene expression increases with aging also in the islets of our control WT mice (Fig EV6B).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the histological staining for the macrophage marker F4/80, the mRNA expression levels of F4/80 ( Adgre1 ) and the other macrophage markers, CD68 and Itgax, are higher in the isolated islets from Glo1 KD mice compared with WT mice. Although these are extensively used as macrophage markers (Marchetti, 2016; Chan et al , 2019; He et al , 2019; Mukhuty et al , 2021), CD68 has been found to be increased in aged and β‐Gal + β‐cells (Aguayo‐Mazzucato et al , 2017, 2019; Ebrahimi et al , 2020). In line with this, CD68 gene expression increases with aging also in the islets of our control WT mice (Fig EV6B).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that macrophages infiltrate pancreatic islets in T2D patients and model animals, such as Goto‐Kakizaki rats, db / db mice, and high‐fat d‐fed mice [ 28 , 42 , 43 ]. Communication between macrophages and β‐cells in the inflammatory islet microenvironment is mediated by proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…This is an attractive hypothesis that is compatible with the observed increase in islet macrophages in diabetic db/db mice, but not ob/ob compensating mice. Interestingly, macrophages from diabetic db/db islets also displayed a distinct proinflammatory gene expression pattern in comparison to those from ob/ob islets [165].…”
Section: Unsettled Questions and Future Research Directionsmentioning
confidence: 96%